The Role Of International Criminal Court In Command Responsibility Towards Benjamin Netanyahu At Israeli-Palestine Conflict - Ivana, Akiko (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The Israel-Palestine conflict remains one of the most protracted and contentious issues in international relations, particularly regarding violations of human rights and international humanitarian law. In this context, the role of the International Criminal Court (ICC) is crucial in upholding the principle of accountability for serious crimes, including those committed by high-ranking state officials. This article aims to analyze the extent to which the ICC can hold Benjamin Netanyahu, the Prime Minister of Israel, criminally responsible under the doctrine of command responsibility for alleged war crimes committed during the Israel-Palestine conflict, especially in the Gaza region. This study adopts a normative-juridical approach by examining the Rome Statute, official ICC documents, and international investigative reports related to the conflict. The findings indicate that the ICC has jurisdiction to investigate alleged war crimes and crimes against humanity in the Palestinian territories following Palestine’s accession to the Rome Statute in 2015. However, political challenges and the lack of cooperation from non-member states such as Israel remain significant obstacles to legal proceedings. Nonetheless, recent developments suggest growing ICC attention to individual accountability, including for senior government officials who may bear command responsibility for military operations resulting in civilian casualties. In conclusion, while the ICC holds potential as a vital instrument for enforcing international justice, its effectiveness is largely dependent on global political support and the consistent, independent cooperation of member states.